Using Theology to Legitimise Jihadist Radicalism - Huzaifah Bin Othman Alkaff, Syed (S. Rajaratnam School of International Studies 2018)
This article reviews and rebuts the theological justification of suicide bombing by terrorist groups like Al-Qaeda and the socalled Islamic State (IS). It argues that the justification forwarded by these extremist groups is erroneous by exposing the discrepancy in the analogy between acts of inghimas (self-immersion into enemy ranks), the key argument used in the justification, and contemporary forms of suicide attacks.
Keywords: Radicalismo; Terrorismo; Yihad